Semysinthetic biflavonoid Morelloflavone-7,4′,7″,3‴,4‴-penta-O-butanoyl is a more potent inhibitor of Proprotein Convertases Subtilisin/Kexin PC1/3 than Kex2 and Furin - de Souza, Aline Aparecida; de Andrade, Débora Martins; Siqueira, Fábio da Silva; Di Iorio, Juliana Fortes; Veloso, Marcia Paranho; Coelho, Camila de Morais; Viegas Junior, Claudio; Gontijo, Vanessa Silva; dos Santos, Marcelo Henrique; Meneghetti, Maria Cecília Zorél; Nader, Helena Bonciani; Tersariol, Ivarne Luis dos Santos; et al. (Biochimica et biophysica acta. General subjects, 2021)
Garcinia brasiliensis is a species native to the Amazon forest. The white mucilaginous pulp is used in folk medicine as a wound healing agent and for peptic ulcer, urinary, and tumor disease treatments. The activity of the proprotein convertases (PCs) Subtilisin/Kex is associated with the development of viral, bacterial and fungal infections, osteoporosis, hyperglycemia, atherosclerosis, cardiovascular, neurodegenerative and neoplastic diseases. Morelloflavone (BF1) and semisynthetic biflavonoid (BF2, 3 and 4) from Garcinia brasiliensis were tested as inhibitor of PCs Kex2, PC1/3 and Furin, and determined IC50, Ki, human proinflammatory cytokines secretion in Caco-2 cells, mechanism of inhibition, and performed molecular docking studies. Biflavonoids were more effective in the inhibition of neuroendocrine PC1/3 than mammalian Furin and fungal Kex2. BF1 presented a mixed inhibition mechanism for Kex2 and PC1, and competitive inhibition for Furin. BF4 has no good interaction with Kex2 and Furin since carboxypropyl groups results in steric hindrance to ligand-protein interactions. Carboxypropyl groups of BF4 promote steric hindrance with Kex2 and Furin, but effective in the affinity of PC1/3. BF4 was more efficient at inhibiting PCl/3 (IC50 = 1.13 μM and Ki = 0,59 μM, simple linear competitive mechanism of inhibition) than Kex2, Furin. Also, our results strongly suggested that BF4 also inhibits the endogenous cellular PC1/3 activity in Caco-2 cells, since PC1/3 inhibition by BF4 causes a large increase in IL-8 and IL-1β secretion in Caco-2 cells. BF4 is a potent and selective inhibitor of PC1/3. BF4 is the best candidate for further clinical studies on inhibition of PC1/3. [Display omitted] •Biflavonoids from Garcinia brasiliensis are able to inhibit proprotein convertases.•Semisynthetic biflavonoid BF4 is a potent inhibitor of PC1/3 protease.•BF4 do not perform good molecular interactions with Kex2 and Furin.•BF4 increase pro-inflammatory IL-8 and IL-β1 secretion in Caco-2 cells.•Medicinal plants are a source of molecules against pathologies involving PCs.